PEMANFAATAN RIMPANG KUNIR PUTIH (Curcuma zedoaria) SEBAGAI PENGURANG KERUSAKAN STRUKTUR MIKROANATOMI HEPAR MENCIT AKIBAT ALKOHOL - Lisdiana Lisdiana (The East Java Biological Society, 2004)
Curcuma zedoaria, familia Zingiberaceae, has been used for along time as an alternative healing. active compounds within it are coneol, comphene, borneol, camphor, zedoarin, resin, gum, and curcumin. Curcumin is an antioxidan that can slow cell damages caused by toxicant. The purpose of this research was to find out the role of Curcuma zedoaria’s rhizome for minimizing damage of microanatomical structure of liver caused by alcoholic toxicant. Samples in the research were 24 mice (Mus musculus) Swiss Webster. They were grouped randomly into 8 groups. Each group was treated as follow. Group A (control group) was given fresh water. Group B was given whisky. Group C was given 500 mg Curcuma zedoaria/kg body weight. Group D was given 750 mg Curcuma zedoaria/kg body weight. Group E was given Curcuma zedoaria/kg body weight. Group F was given whisky and, 2 hours later, 500 mg Curcumazedoaria/kg body weight. Group G was given whisky and, 2 hours later, 750 mg Curcuma zedoaria/kg body weight. The last group was given whisky and, 2 hours later, 1000 mg Curcuma zedoaria/kg body weight. The treatment was carried out during 8 days. A microanatomy slide of liver was made by using parafin method and Hematoxylin-Eosin dying. Data was analyzed by using descriptive method, comparing between the control group and the experiment groups.The result of the research showed that the powder of the Curcuma zedoaria’s rhizome has been useful in minimizing damage of hepar microanatomy structure of the mice affected by alcohol. The effective dosage was 1000 mg/kg body weight.